PEMANFAATAN GULMA TITONIA (Tithonia diversifolia) SEBAGAI PUPUK ORGANIK PADA TANAMAN JAGUNG MANIS - Ikhsan Hasibuan; Sarina Sarina; Anggia Damayanti (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2021)
Tithonia (Tithonia diversifolia) is an invasive weed plant commonly grown in Asia and Africa, including in Bengkulu Province. As a weed, this plant is rarely used in agricultural production though it has great potential to be used as the primary source for organic fertilizer. This study aimed to evaluate the effects of doses and application frequency of organic fertilizer made of tithonia on the growth and yield of sweet corn. An experiment had been carried out in Bengkulu Province from September 2019 until February 2020. The research comprised three levels of organic fertilizer rates and two levels of application frequencies replicated thrice in Completely Randomized Design with LSD 5%. The results showed that tithonia organic fertilizer did not influence the plant heights of sweet corn but had significant effects on the dry weight of shoot and root. Tithonia organic fertilizer had fulfilled the minimum requirement as organic fertilizer as obliged in the national organic standard (SNI). The highest yield of sweet corn was obtained by applying 20 t/ha of tithonia organic fertilizer in the twice split application.